Financing Local Governments in South Africa - De Visser, Jaap (Anuario de Derecho Municipal, 2024)
The intergovernmental fiscal architecture for local governments in South Africa is a product of the negotiations in the late 1990ties to end apartheid, a thorough consideration at the time of what funding system for local government would serve a democratic South Africa the best, and the many developments that the system has undergone since its inception around the turn of the century. The architecture reflects South Africa’s integrated system of multilevel government. The national government has a virtual monopoly on all taxes, and provinces almost rely almost entirely on transfers. Municipalities fund their budgets with own revenue, complemented by an equitable share of national revenue and conditional grants. This contribution sets out the considerations that influenced the system of financing local government, designed to usher in democracy at local level. It then examines the framework for own revenue generation by municipalities as well as the system for determining intergovernmental transfers. It considers practical challenges with the implementation of this framework, the extent to which the assumptions that underpin the architecture are still valid, and the system’s capacity to respond to changing circumstances.